Study on Compaction and Machinability of Silicon Nitride (Si3N4) Reinforced Copper Alloy Composite through P/M Route. (8th July 2021) - Sathish, T.; Mohanavel, V.; Karthick, Alagar; Arunkumar, M.; Ravichandran, M.; Rajkumar, S.
Abstract : Nowadays, most of the products are used in the electrical and electronics field, and copper alloy is playing a significant role such as Springs for relay contacts and switchgear, Rotor bars, and Busbars. In this work, the copper alloys consider as base alloy, and the reinforced factor of silicon nitride (Si3 N4 ) is processed of reinforcement as 3 wt. %, 6 wt. %, 9 wt. %, 12 wt. % Si3 N4 through powder metallurgy performance. The ball mill process is used for this work to obtain an enhanced homogeneous mixture of both base material as well as reinforced particles. Using a hydraulic press, the blended powders are compacted with applying 3 kN and 10 min period for obtained good strength of green compact specimens. Further, the green compacted specimens are sintered, and the sintered billets are machined in the conventional lathes with different cutting speeds 50 m/min, 100 m/min, and 150 m/min; feed rate of 0.1 mm/rev (fixed); and depth of cut of 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.4 mm, and 1.6 mm. Cutting speed and depth of cut to find the composites' cutting force is ingenious. A wear test also can be conducted to find the wear resistance of the reinforced particles of the copper alloy material.